INFLUENCE OF WINDOW TYPE ON THE AIRTIGHTNESS OF RESIDENTIAL UNITS (Advances in Civil and Architectural Engineering, 2021)
Airtightness plays a significant role in the energy efficiency of buildings. In this paper, we investigated how varying the type of window affects the airtightness values of residential units. We studied three sets of residential units, each comprising two residential units with the same geometry and year of construction, varying only the installed window type and window-frame material. A brief explanation is included of the blower-door method, used in field-testing the airtightness of residential units. Replacing the old windows in the residential units with newer windows significantly improved the airtightness. To generalize these results, further research is needed with larger samples.